BS EN 50288-13-2. Multi-element metallic cables used in analogue and digital communication and control. Part 13-2. Sectional specification for outer screened cables characterised from 1 MHz up to 2000 MHz. Work Area cable (19th May 2020) - British Standards Institution,
No abstract available